Positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

By introducing high Ni content of lithium transition metal composite oxide and specific metal elements into the positive electrode active substance of lithium-ion batteries, and combining specific conductive additives to form a layered positive electrode mixture layer, the problems of high internal resistance and low durability of the battery are solved, and more efficient fast charging and discharge performance and better durability are achieved.

CN119908036APending Publication Date: 2025-04-29PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380067232.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-29
Filing Date
2023-06-28
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

There is room for improvement in the positive electrode active substances of existing lithium-ion batteries to reduce the internal resistance of the battery, especially in the high SOC state, which is prone to side reactions and lead to a decrease in durability.

Method used

A lithium transition metal composite oxide containing more than 75 mol% Ni is used as the positive electrode active substance, and metal elements such as Ca and Sr are introduced on the surface of its particles, and combined with a specific conductive additive, a positive electrode mixture layer with a layered structure is formed to reduce the reaction resistance.

Benefits of technology

It effectively suppresses side reaction with the electrolyte, reduces the reaction resistance of the positive electrode, and improves the fast charging and discharge performance and durability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119908036A_ABST
    Figure CN119908036A_ABST
Patent Text Reader

Abstract

In a nonaqueous electrolyte secondary battery (10), which is an example of an embodiment, a positive electrode (11) contains, as a positive electrode active material, a lithium transition metal composite oxide having a layered structure and containing at least 75 mol% of Ni with respect to the total molar amount of metal elements other than Li. The lithium transition metal composite oxide is a secondary particle formed by aggregating primary particles, and at least one element selected from the group consisting of Ca and Sr and at least one element selected from the group consisting of W, Mo, Ti, Si, Nb, and Zr are present at the interface between the primary particles inside the secondary particle. The conductive auxiliary agent in the positive electrode mixture layer (31) contains carbon and contains at least one substance selected from the group consisting of a particulate carbon material having an average particle diameter of 20 nm or less and a fibrous carbon material having an average fiber diameter of 20 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery using the positive electrode. Background Art

[0002] In recent years, secondary batteries such as lithium-ion batteries have been widely used in applications such as vehicle-mounted applications and power storage applications that require high capacity, high durability, and fast charge and discharge performance. The positive electrode active material, which is the main component of the secondary battery, significantly affects these properties, so a lot of research has been done on the positive electrode active material. For example, in Patent Document 1, as an active material for a non-aqueous electrolyte secondary battery, a lithium transition metal composite oxide is disclosed, which has an α-NaFeO2 structure and contains one or more transition metal elements selected from the group consisting of Mn, Ni and Co, and alkaline earth metals and W are present on the particle surface.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-129221 Summary of the invention

[0006] In secondary batteries such as lithium-ion batteries, reducing internal resistance, for example, improving output characteristics to enhance rapid charge and discharge performance is an important technical issue. Conventional positive electrode active materials, including Patent Document 1, still have much room for improvement in reducing battery internal resistance.

[0007] Regarding the positive electrode active material for secondary batteries involved in the present disclosure, for a positive electrode for a non-aqueous electrolyte secondary battery having a positive electrode core and a positive electrode mixture layer formed on the positive electrode core, the positive electrode mixture layer includes a positive electrode active material, a conductive auxiliary agent and a binder, and the positive electrode active material includes a lithium transition metal composite oxide, the lithium transition metal composite oxide has a layered structure, and contains Ni of 75 mol% or more relative to the total molar amount of metal elements other than Li. The lithium transition metal composite oxide is a secondary particle formed by the aggregation of primary particles, and at the interface between the primary particles inside the secondary particles, there is at least one selected from the group consisting of Ca and Sr and at least one selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. The conductive auxiliary agent contains carbon and includes at least one selected from the group consisting of a granular carbon material having an average particle size of less than 20nm and a fibrous carbon material having an average fiber diameter of less than 20nm.

[0008] The nonaqueous electrolyte secondary battery according to the present disclosure includes the above-mentioned positive electrode, a negative electrode, and a nonaqueous electrolyte.

[0009] According to the positive electrode active material according to the present disclosure, the internal resistance of the nonaqueous electrolyte secondary battery can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is a diagram schematically showing an axial cross section of a nonaqueous electrolyte secondary battery (cylindrical battery) as an example of an embodiment. DETAILED DESCRIPTION

[0011] Lithium transition metal composite oxides with high Ni content have attracted attention as positive electrode active materials for non-aqueous electrolyte secondary batteries. It is known that lithium transition metal composite oxides with high Ni content contribute to high battery capacity, but when used as positive electrode active materials, especially in high SOC (State Of Charge) conditions, a large amount of highly reactive Ni is present on the particle surface. 4+ , so it is easy to have a side reaction with the electrolyte. As a result, the deposition of decomposed products and the dissolution of transition metals occur at the positive electrode, and there is a tendency for durability to decrease.

[0012] The research results of the present inventors show that by introducing specific metal elements at the interface between the primary particles constituting the positive electrode active material, the side reaction with the electrolyte is effectively suppressed, and the reaction resistance from the positive electrode is successfully reduced. On the other hand, it is found that the following technical problems exist: the electronic conductivity of the compounds containing these elements is low, and the conductive path cannot be fully formed in the widely used conventional conductive aids such as carbon black. To this end, in order to solve this technical problem, the present inventors conducted in-depth research and found that by combining conductive aids with special microstructures, the DC resistance component of the battery can be reduced, and the overall resistance of the battery can be further improved.

[0013] Hereinafter, with reference to the accompanying drawings, an example of an embodiment of a positive electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery using the positive electrode according to the present disclosure will be described in detail. It should be noted that a method of selectively combining the constituent elements of the multiple embodiments and variations described below is also included in the scope of the present disclosure.

[0014] In the embodiment described below, a cylindrical battery 10 in which a wound electrode body 14 is contained in an outer can 16 with a bottomed cylindrical shape is exemplified, but the outer body of the battery is not limited to a cylindrical outer can. As other embodiments of the non-aqueous electrolyte secondary battery involved in the present disclosure, a square battery with a square outer can, a coin-shaped battery with a coin-shaped outer can, and a bag-type battery with an outer body composed of a laminate sheet including a metal layer and a resin layer can be listed. In addition, the electrode body is not limited to a wound type, and can also be a stacked electrode body in which multiple positive electrodes and multiple negative electrodes are alternately stacked with separators.

[0015] Figure 1 1 is a cross-sectional view of a cylindrical battery 10 as an example of an embodiment. Figure 1 As shown, the cylindrical battery 10 includes a wound electrode body 14, an electrolyte, and an outer can 16 for accommodating the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the outer can 16 is blocked by a sealing body 17. In the following, for the convenience of explanation, the sealing body 17 side of the battery is set as the upper side, and the tank bottom side of the outer can 16 is set as the lower side.

[0016] The non-aqueous electrolyte is not limited to a liquid electrolyte (electrolyte), but may also be a solid electrolyte. In the present embodiment, a non-aqueous electrolyte is used. The non-aqueous electrolyte comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may, for example, use esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. As an example of a non-aqueous solvent, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and mixed solvents thereof may be cited. The non-aqueous solvent may contain a halogen substitute (e.g., fluoroethylene carbonate, etc.) formed by replacing at least a portion of hydrogen in these solvents with halogen atoms such as fluorine. The electrolyte salt may, for example, use a lithium salt such as LiPF6.

[0017] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, which are alternately stacked in the radial direction of the electrode body 14 by being wound into a spiral shape. In order to prevent the precipitation of lithium, the negative electrode 12 is formed to be one circle larger than the positive electrode 11. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged in a manner of sandwiching the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.

[0018] Insulating plates 18 and 19 are disposed above and below the electrode body 14, respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the lid 27 electrically connected to the internal terminal plate 23, becomes the positive terminal. The negative electrode lead 21 is connected to the inner surface of the bottom of the outer can 16 by welding or the like, and the outer can 16 becomes the negative terminal.

[0019] A sealing gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed on the outer can 16 so that a part of the side portion bulges inward and supports the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumference of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 through the groove portion 22 and the open end portion of the outer can 16 that is closely fitted with the sealing body 17.

[0020] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating component 25, an upper valve body 26, and a lid 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating component 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating component 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heating, the lower valve body 24 is deformed and broken to push the upper valve body 26 to the lid 27 side, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the lid 27.

[0021] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 , in particular, the positive electrode active material and the conductive auxiliary agent constituting the positive electrode 11 will be described in detail.

[0022] [positive electrode]

[0023] The positive electrode 11 has a positive electrode core 30 and a positive electrode mixture layer 31 disposed on the positive electrode core 30. The positive electrode core 30 can be made of a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film having the metal disposed on the surface, or the like. The positive electrode mixture layer 31 contains a positive electrode active material, a binder, and a conductive additive, and is preferably disposed on both surfaces of the positive electrode core 30 except for the portion connected to the positive electrode lead 20. The positive electrode 11 can be manufactured, for example, by coating a positive electrode mixture slurry containing a positive electrode active material, a binder, and a conductive additive on the surface of the positive electrode core 30, drying the coating, and then compressing the coating to form the positive electrode mixture layer 31 on both surfaces of the positive electrode core 30.

[0024] The positive electrode 11 includes a lithium transition metal composite oxide as a positive electrode active material, the lithium transition metal composite oxide having a layered structure and containing 75 mol% or more of Ni relative to the total molar amount of metal elements other than Li. As described in detail later, the lithium transition metal composite oxide is a secondary particle formed by the aggregation of primary particles. In addition, at the interface between the primary particles inside the secondary particles, there is at least one selected from the group consisting of Ca and Sr and at least one selected from the group consisting of W, Mo, Ti, Si, Nb and Zr.

[0025] The positive electrode active material may have the above-mentioned lithium transition metal composite oxide (hereinafter referred to as "composite oxide (Z)") as a main component, or may be substantially composed of only the composite oxide (Z). It should be noted that, within the scope of the purpose of the present disclosure, the positive electrode active material may contain composite oxides or other compounds other than the composite oxide (Z). The content of the composite oxide (Z) is preferably 50% by mass or more of the total mass of the positive electrode active material, and may also be 70% by mass or more, 80% by mass or more, or substantially 100% by mass.

[0026] The composite oxide (Z) has, for example, a layered rock salt structure. Examples of the layered rock salt structure include a layered rock salt structure belonging to the space group R-3m, a layered rock salt structure belonging to the space group C2 / m, and the like. Among them, from the perspective of high capacity and stability of the crystal structure, a layered rock salt structure belonging to the space group R-3m is preferred.

[0027] The composite oxide (Z) is a secondary particle formed by the aggregation of primary particles. The volume-based median particle size (D50) of the composite oxide (Z) is, for example, greater than 3 μm and less than 30 μm, preferably greater than 5 μm and less than 25 μm. Since the composite oxide (Z) is a secondary particle formed by the aggregation of primary particles, the D50 of the composite oxide refers to the D50 of the secondary particle. D50 refers to the particle size when the cumulative frequency reaches 50% from the side with a smaller particle size in the volume-based particle size distribution, also known as the median diameter. The particle size distribution of the composite oxide (Z) can be measured using a laser diffraction particle size distribution measuring device (e.g., MT3000II manufactured by Microtrac Bell) and water as a dispersion medium. In addition, the particle size distribution of the positive electrode active material can be measured using an image-based particle size distribution measuring device (e.g., CAMSIZER X2 manufactured by Microtrac Bell) and water as a dispersion medium.

[0028] The average particle size of the primary particles constituting the composite oxide (Z) is, for example, 0.02 μm or more and 1 μm or less, preferably 0.05 μm or more and 0.8 μm or less. The average particle size of the primary particles is obtained as follows: a cross section of the secondary particles is photographed using a scanning electron microscope (SEM), the diameter of 100 circumscribed circles of the primary particles extracted by analyzing the SEM image is measured, and the measured values ​​are averaged for calculation. The cross section of the secondary particles can be prepared by a cross section polishing (CP) method.

[0029] The composite oxide (Z) is, for example, of the general formula Li x Ni a Co b Mn c Al d M1 e M2 f O2-y The composite oxide shown in the formula, wherein 0.95<x<1.05, 0.75≤a≤0.95, 0≤b≤0.15, 0≤c≤0.25, 0≤d≤0.03, 0<e≤0.01, 0<f≤0.03, 0≤y<0.05, a+b+c+d+e+f=1, M1 is at least one element selected from the group consisting of Ca and Sr, and M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. The content of the elements in the composite oxide (Z) can be measured by an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron beam microanalyzer (EPMA) or an energy dispersive X-ray analyzer (EDX).

[0030] The composite oxide (Z) preferably contains Ni in an amount of 75 mol% or more relative to the total molar number of metal elements other than Li. By setting the Ni content to 75 mol% or more, a high-capacity battery can be obtained, and the effect of adding the above-mentioned metal elements M1 and M2 can be made more significant. That is, it can be considered that when a composite oxide (Z) with a high Ni content is used as a positive electrode active material, although a large amount of highly reactive Ni is present on the particle surface, 4+ , but due to the effects of metal elements M1 and M2, Ni 4+ The influence of can be sufficiently reduced. The content of Ni can be 80 mol% or more, or 85 mol% or more relative to the total molar number of metal elements other than Li. The upper limit of the content of Ni is, for example, 95 mol%.

[0031] The composite oxide (Z) preferably further contains at least one selected from the group consisting of Mn and Co. As a preferred example of the composite oxide (Z), a lithium nickel composite oxide containing Mn, a lithium nickel composite oxide containing Mn and Co, or a lithium nickel composite oxide containing Co and Al can be cited. When the composite oxide (Z) contains Mn, the content of Mn is preferably 1 mol% or more and 25 mol% or less relative to the total molar number of metal elements other than Li, and more preferably 5 mol% or more and 20 mol% or less. In this case, it is easy to take into account both high capacity and high durability of the battery.

[0032] When the composite oxide contains Co, the content of Co is preferably 1 mol% or more and 15 mol% or less relative to the total molar number of metal elements other than Li, and more preferably 2 mol% or more and 7 mol% or less. In this case, it is easy to take into account both high capacity and high durability while suppressing material costs. When the composite oxide (Z) contains Al, the content of Al is, for example, 0.1 mol% or more and 5 mol% or less relative to the total molar number of metal elements other than Li.

[0033] The composite oxide (Z) also contains metal elements M1 and metal elements M2 as essential components. As described above, the metal element M1 is at least one element selected from the group consisting of Ca and Sr, and the metal element M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. It can be considered that by adding a small amount of M1 and M2 to the composite oxide (Z), side reactions can be suppressed, the reaction resistance from the positive electrode can be reduced, and the charge and discharge cycle characteristics can be effectively improved. It should be noted that if only one of M1 and M2 is added, a sufficient effect cannot be obtained.

[0034] The metal element M1 is present at the interface between the primary particles at least inside the secondary particles of the composite oxide (Z), for example, it is present at a higher density on the surface than inside the primary particles. The M1 present on the surface of the primary particles can be confirmed by TEM-EDX and STEM-EDX. M1 is present at the interface between the primary particles, for example, in a uniformly dispersed state. It should be noted that M1 can also be fixed to the surface of the secondary particles (the surface of the primary particles present on the surface of the secondary particles).

[0035] Even a very small amount of the metal element M1 is effective, but the lower limit of its content is preferably 0.05 mol%, more preferably 0.1 mol%, relative to the total molar number of metal elements other than Li in the composite oxide (Z). In addition, the content of M1 is preferably less than 1 mol% relative to the total molar number of metal elements other than Li. Even if more than 1 mol% of M1 is added, the improvement effect of the cycle characteristics is small, or the cycle characteristics are deteriorated. Adding more than 1 mol% of M1, for example, will lead to problems such as increased resistance and decreased charging capacity.

[0036] The content of the metal element M1 is preferably 0.05 mol% to 1 mol%, more preferably 0.1 mol% to 0.7 mol% or 0.2 mol% to 0.5 mol%. When Ca and Sr are added as M1, the total of their contents is preferably within this range.

[0037] Even if the metal element M2 is very small, it is effective, but the lower limit of its content is preferably 0.05 mol%, more preferably 0.1 mol%, relative to the total molar number of metal elements other than Li in the composite oxide (Z). In addition, the content of M2 can be the same as the content of M1 or higher than the content of M1, and is preferably less than 3 mol% relative to the total molar number of metal elements other than Li. Even if more than 3 mol% of M2 is added, the improvement effect of the cycle characteristics is small, or the cycle characteristics are deteriorated. In addition, adding more than 3 mol% of M2, for example, will lead to problems such as increased resistance and decreased charging capacity.

[0038] The content of the metal element M2 is, for example, lower than the content of Mn and higher than the content of M1. An example of a preferred content of M2 is 0.05 mol% to 1 mol%, more preferably 0.2 mol% to 0.8 mol% or 0.3 mol% to 0.7 mol%. When two or more elements are added as M2, it is preferred that the sum of their contents is within this range.

[0039] As described above, the metal element M2 is at least one selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. All of these elements may be added to the composite oxide (Z), but preferably three or less elements are added. Among them, W, Ti, Nb and Zr are preferred. When two types of M2 are added, Nb and Zr, Nb and Ti, Nb and W, W and Ti, and W and Zr can be listed as preferred combinations of M2.

[0040] Metal element M2 is present at the interface between primary particles in the secondary particles of composite oxide (Z) in the same manner as metal element M1, and is present at a higher density on the surface than in the primary particles. It should be noted that M2 can form a solid solution with other metal elements such as Ni. The solid solution amount of M2 can be confirmed by inductively coupled plasma emission spectrometry (ICP-AES) or energy dispersive X-ray spectroscopy (EDS).

[0041] At the interface between primary particles inside the secondary particles of the composite oxide (Z), for example, a particle of the general formula M1 is fixed. α M2 β O γ The compound shown in the formula, wherein 1≤α≤2, 1≤β≤5, 4≤γ≤9, M1 is at least one element selected from the group consisting of Ca and Sr, and M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. In this case, M1 and M2 are contained in the same compound.

[0042] At least one compound selected from the group consisting of the following first compound, second compound and third compound may be fixed to the surface of the primary particle of the composite oxide (Z). An example of the third compound is the above-mentioned general formula M1 α M2 β O γ The compounds shown.

[0043] First compound: a compound containing at least one selected from the group consisting of Ca and Sr

[0044] Second compound: a compound containing at least one selected from the group consisting of W, Mo, Ti, Si, Nb and Zr

[0045] Third compound: a compound containing at least one selected from the group consisting of Ca and Sr and at least one selected from the group consisting of W, Mo, Ti, Si, Nb, and Zr

[0046] It should be noted that the composite oxide (Z) may contain other elements besides Li, Ni, Co, Mn, Al, M1, M2, and O. Examples of such other elements include Cu, Mg, Na, K, Ba, Fe, B, and P. When other elements are contained, their content is preferably 1 mol% or less relative to the total molar number of metal elements except Li.

[0047] The composite oxide (Z) can be synthesized, for example, by mixing and calcining an oxide containing at least Ni, preferably other metal elements such as Mn, Co, and Al, an M1 raw material, an M2 raw material, and a Li raw material. The composite oxide (Z) is obtained by crushing the calcined product and washing it with water. It should be noted that the water washing step can also be omitted. As an example of a Li raw material, Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, LiF, etc. can be listed. The oxide containing Ni and the like and the Li raw material are preferably mixed at a ratio of 1:0.98 to 1:1.12 in the molar ratio of the total amount of metal elements other than Li in the oxide to Li in the Li raw material.

[0048] Examples of M1 raw materials include Ca(OH)2, CaHPO4, Ca(H2PO4)2, Ca3(PO4)2, CaO, CaCO3, CaSO4, and Ca(NO3). 2、 CaCl2, CaAlO4, Sr(OH)2, Sr(OH)2·8H2O, SrO, SrCO3, SrSO4, Sr(NO3)2, etc. Examples of M2 raw materials include Nb2O5, Nb2O5·nH2O, WO3, Li2WO4, TiO2, Ti(OH)4, ZrO2, Zr(OH)4, MoO3, Li2MoO4, SiO, SiO2, etc.

[0049] The calcination process of the above-mentioned mixture is, for example, a multi-stage calcination process including at least a first calcination process and a second calcination process having a temperature higher than that of the first calcination process. In addition, the calcination of the mixture is carried out under an oxygen atmosphere, and at this time, for example, the oxygen concentration is set to 85% or more. The preferred first calcination temperature varies depending on the composition of the mixture, but as an example, it is 500°C or more and 680°C or less. The preferred second calcination temperature is, for example, 700°C or more and 850°C or less. It is preferred that there is a temperature difference of 50°C or more between each calcination process.

[0050] The roasting process is carried out by putting the above mixture into a roasting furnace. The roasting process may include a plurality of heating steps with different heating rates. For example, the temperature may be raised from room temperature to a first roasting temperature (first heating step) at a rate of 1.0°C / minute or more and 5.5°C / minute or less, and the temperature may be raised from the first roasting temperature to a second roasting temperature (second heating step) at a rate of 0.1°C / minute or more and 3.5°C / minute or less slower than the first heating step. The maximum reaching temperature of the roasting process may be maintained for a predetermined time (e.g., 1 hour or more and 10 hours or less).

[0051] In the following water washing step, the calcined product obtained in the calcining step is washed with water to remove impurities, and the washed calcined product is heated and dried. As needed, the calcined product is crushed, classified, etc., and the D50 of the positive electrode active material is adjusted to the target range. The calcined product after water washing can also be dried at a temperature of less than 100°C. An example of a preferred drying temperature is 150°C to 250°C. The drying process can be carried out both under vacuum and in the atmosphere. An example of the drying process time is 1 hour to 5 hours.

[0052] The composite oxide (Z) is obtained by precipitating (coprecipitating) a composite hydroxide containing Ni and any metal element and heat-treating the composite hydroxide. The composite hydroxide can be synthesized, for example, by adding an alkaline solution such as sodium hydroxide while stirring a solution of a metal salt containing Ni and any metal element (Co, Al, Mn, M2, etc.) and adjusting the pH to the alkaline side (for example, 8.5 or more and 12.5 or less). There is a tendency that the higher the pH during synthesis, the smaller the particle size of the composite hydroxide. In addition, the particle size of the composite hydroxide can also be controlled by adjusting the amount of solution of the added metal salt, for example, there is a tendency that the more the amount of solution, the larger the particle size. The particle size of the composite oxide (Z) can be adjusted, for example, by controlling the particle size of the precursor, i.e., the composite hydroxide. The heat treatment temperature is not particularly limited, for example, in the range of 250°C to 600°C.

[0053] As described above, the positive electrode mixture layer 31 includes a binder and a conductive aid. As a binder, fluorinated polymers such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be listed. In addition, these resins can be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc. The content of the binder is, for example, 0.1 mass parts or more and 2 mass parts or less relative to 100 mass parts of the positive electrode active material, preferably 0.5 mass parts or more and 1.5 mass parts or less.

[0054] The conductive aid contains carbon and includes at least one selected from the group consisting of a granular carbon material having an average particle size of 20 nm or less and a fibrous carbon material having an average fiber diameter of 20 nm or less. The positive electrode mixture layer 31 may include a carbon material having an average particle size / average fiber diameter greater than 20 nm as a conductive aid, but a granular carbon material having an average particle size of 20 nm or less or a fibrous carbon material having an average fiber diameter of 20 nm or less is used as a main component. It should be noted that the main component refers to the component with the largest mass proportion in the conductive aid.

[0055] The conductive aid may be substantially composed of only at least one selected from the group consisting of a granular carbon material having an average particle size of less than 20 nm and a fibrous carbon material having an average fiber diameter of less than 20 nm. Typically, carbon blacks such as acetylene black are composed of the smallest particles called domains or particles, primary aggregates formed by the aggregation of these smallest particles, and secondary aggregates formed by the aggregation of primary aggregates. Here, primary aggregates are generally referred to as microstructures (structure) or aggregates (aggregates), and secondary aggregates are also generally referred to as agglomerates, etc. The average particle size in the present disclosure refers to the average particle size of the above-mentioned smallest particles. In addition, the aspect ratio (ratio of the major diameter to the minor diameter) of carbon blacks such as acetylene black refers to the aspect ratio of the primary aggregates. It should be noted that when the average particle size / average fiber diameter of the conductive aid contained in the positive electrode mixture layer 31 is greater than 20 nm, a sufficient resistance reduction effect cannot be obtained. As described above, the positive electrode mixture layer 31 may contain a carbon material having an average particle size / average fiber diameter greater than 20 nm as a conductive additive. However, the average particle size / average fiber diameter of the conductive additive contained in the positive electrode mixture layer 31 needs to be 20 nm or less.

[0056] The above-mentioned granular carbon material can be Ketjen black, furnace black, graphite, etc., but is preferably acetylene black (AB). An example of a preferred granular carbon material is AB with an average particle size of less than 20 nm. The average particle size of AB is obtained by image analysis using a transmission electron microscope (TEM). The average particle size of AB is obtained by arbitrarily selecting 100 ABs, measuring the major diameter of the smallest particle and calculating the arithmetic average of the measured values. The lower limit of the average particle size of AB is not particularly limited, and as an example, it is 1 nm. The aspect ratio of AB is, for example, more than 1.2 times and less than 2.5 times or more than 1.3 times and less than 2 times.

[0057] The content of the granular carbon material (AB) is preferably less than 2 parts by mass, more preferably less than 1.5 parts by mass, and may be less than 1 part by mass relative to 100 parts by mass of the positive electrode active material. Even if AB is a small amount, a good conductive path is formed in the positive electrode mixture layer 31, but the lower limit of the content is preferably 0.1 parts by mass, more preferably 0.2 parts by mass. An example of a preferred content of AB is 0.2 parts by mass or more and 1.5 parts by mass or less or 0.5 parts by mass or more and 1.2 parts by mass relative to 100 parts by mass of the positive electrode active material.

[0058] The above-mentioned fibrous carbon material can be carbon nanofiber (CNF) etc., preferably carbon nanotube (CNT). CNT is a conductive carbon fiber with a fiber diameter, i.e., an outer diameter of a tube, of less than tens of nm, having a very large aspect ratio (ratio of fiber length to fiber diameter). The average aspect ratio of CNT is, for example, more than 20 times, preferably more than 50 times. Through the CNT with a high aspect ratio, the contact between the active material and the core material is not point contact but line contact. Therefore, a small amount of addition forms a good conductive path.

[0059] The average fiber diameter of the CNT used in the positive electrode 11 is less than 20nm, preferably less than 15nm, and more preferably less than 10nm. It should be noted that the fiber diameter refers to the length in the direction perpendicular to the fiber length direction. If the average fiber diameter is less than 20nm, the DC resistance is more effectively reduced. The lower limit of the average fiber diameter of CNT is not particularly limited, and is 1nm as an example. The average fiber diameter of CNT is obtained by image analysis using TEM. The average fiber diameter of CNT is obtained by arbitrarily selecting 100 CNTs, measuring the fiber diameter and calculating the arithmetic average of the measured values.

[0060] The average fiber length of CNT is, for example, 0.5 μm or more, and may be 1 μm or more. It should be noted that the fiber length refers to the length when the CNT is stretched into a straight line. If the average fiber length is 0.5 μm or more, the DC resistance is more effectively reduced. The upper limit of the average fiber length of CNT is not particularly limited, and as an example, it is 100 μm. The average fiber length of CNT is obtained by image analysis using a scanning electron microscope (SEM). The average fiber length of CNT is obtained by arbitrarily selecting 100 CNTs, measuring the length and arithmetically averaging the measured values. For CNTs present in the positive electrode, there are also cases where multiple CNTs exist in a bundle state. When calculating the above-mentioned average fiber length, the length of a single CNT present in the bundled CNT is used.

[0061] CNT can be any of single-walled CNT (SWCNT) and multi-walled CNT (MWCNT). As a conductive additive, SWCNT and MWCNT can be used in combination. SWCNT has a structure in which one layer of graphite sheets is formed into a tubular shape, and multi-walled CNT has a structure in which multiple layers of graphite sheets are formed into a tubular shape. An example of multi-walled CNT is a double-walled CNT having a two-layer structure.

[0062] The preferred BET specific surface area of ​​CNT varies depending on the type of CNT, but is 200 m 2 / g or more, more preferably 250m 2 The upper limit of the BET specific surface area is not particularly limited, but is 2000 m 2 The BET specific surface area is measured according to the BET method (nitrogen adsorption method) described in JIS R1626.

[0063] The content of fibrous carbon material (CNT) is preferably 2 parts by mass or less, more preferably 1 part by mass or less relative to 100 parts by mass of the positive electrode active material. Even if CNT is a small amount, it forms a good conductive path in the positive electrode mixture layer 31, but the lower limit of the content is preferably 0.01 parts by mass, more preferably 0.05 parts by mass. An example of a preferred CNT content is 0.1 parts by mass or more and 1 part by mass or less or 0.2 parts by mass or more and 0.7 parts by mass or less relative to 100 parts by mass of the positive electrode active material.

[0064] CNT is supplied to the manufacturing process of the positive electrode 11 in the state of a conductive auxiliary agent dispersion dispersed in a liquid containing a dispersant and an aprotic polar solvent (dispersion medium), and is added to the positive electrode mixture slurry. In the dispersion, the dispersant is dissolved in the polar solvent, and the CNT is dispersed in the polar solvent by the action of the dispersant. The solid component (CNT and dispersant) concentration of the dispersion is, for example, 0.1% by mass or more and 20% by mass or less. From the perspective of both the dispersibility and productivity of CNT, it is preferably 0.2% by mass or more and 15% by mass or less, and more preferably 1% by mass or more and 10% by mass or less.

[0065] The D50 of CNTs dispersed in a polar solvent is preferably less than 8 μm, more preferably less than 3 μm. When a dispersion in which the D50 of CNTs is adjusted to less than 8 μm is used to make the positive electrode 11, the DC resistance of the battery can be effectively reduced. The particle size distribution of CNTs can be measured using a laser diffraction particle size distribution measuring device in the same manner as the particle size distribution of the positive electrode active material. The dispersion is prepared by mixing a conductive additive, a dispersant and a non-protonic polar solvent. The mixing (kneading) of these raw materials can use a previously known disperser or mixer, such as a planetary mixer, a homogenizing mixer, a pin mixer, a high-speed mixer, a disperser, a roller mill, a ball mill, a jet mill, a kneader, and the like.

[0066] The dispersant includes, for example, nitrile-containing rubber. The nitrile-containing rubber is a copolymer of monomers containing unsaturated nitrile and conjugated diene as raw materials, and may also be a copolymer of substantially only unsaturated nitrile and conjugated diene. The molar ratio of unsaturated nitrile to conjugated diene is, for example, 10:90 to 70:30. The weight average molecular weight of the nitrile rubber is not particularly limited, and as an example, it is 5000 to 5000000. At least a portion of the dispersant may function as a binder for the positive electrode mixture layer 31.

[0067] The nitrile-containing rubber may be a hydrogenated nitrile rubber. The hydrogenated nitrile rubber may include, for example, a structural unit derived from an unsaturated nitrile, a structural unit derived from a conjugated diene, and a structural unit derived from a hydrogenated conjugated diene. An example of a preferred hydrogenated nitrile rubber is a partially hydrogenated nitrile rubber in which more than 80 mol% of the structural units derived from a conjugated diene are hydrogenated. An example of an unsaturated nitrile is acrylonitrile or methacrylonitrile, preferably acrylonitrile. An example of a conjugated diene is a conjugated diene having 3 to 6 carbon atoms, preferably butadiene.

[0068] The nitrile-based rubber is preferably contained in an amount of 10 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of CNT. The dispersion of CNT can only include nitrile rubber as a dispersant, or other dispersants can be used in combination. The mass ratio of the nitrile rubber in the dispersant is preferably 20% by mass or more, more preferably 30% by mass or more. As other dispersants used in combination with nitrile rubber, polyvinyl alcohol, polyvinyl pyrrolidone (PVP), polyalkylene oxide, polyvinyl acetal, polyvinyl ether, cellulose, chitin, chitosan, starch, and their derivatives can be listed. Among them, PVP or its derivatives (PVP) are preferably used.

[0069] The dispersion medium uses an aprotic polar solvent. The aprotic polar solvent can be any solvent that can dissolve the dispersant and disperse the CNT. Since the dispersion is added to the positive electrode mixture slurry, the polar solvent is preferably a solvent mixed with the solvent of the positive electrode mixture slurry, or it can be a solvent of the same type as the solvent of the positive electrode mixture slurry. As an example of an aprotic polar solvent, N-methyl-2-pyrrolidone (NMP), methyl ethyl ketone, tetrahydrofuran, dimethylformamide, acetone, ethyl acetate, dimethyl sulfoxide, etc. can be listed. Among them, NMP is preferably used.

[0070] [negative electrode]

[0071] The negative electrode 12 includes a negative electrode core 40 and a negative electrode mixture layer 41 disposed on the negative electrode core 40. The negative electrode core 40 may be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a thin film having the metal disposed on the surface. The negative electrode mixture layer 41 includes a negative electrode active material and a binder, and is preferably disposed on both surfaces of the negative electrode core 40 except for the portion connected to the negative electrode lead 21. The negative electrode 12 may be manufactured, for example, by coating a negative electrode mixture slurry including a negative electrode active material and a binder on the surface of the negative electrode core 40, drying the coating, and then compressing the coating to form the negative electrode mixture layer 41 on both surfaces of the negative electrode core 40.

[0072] The negative electrode active material generally uses a carbon material that reversibly absorbs and releases lithium ions. A preferred example of the carbon material is graphite such as natural graphite such as flaky graphite, blocky graphite, and earthy graphite, blocky artificial graphite (MAG), and artificial graphite such as graphitized mesophase carbon microbeads (MCMB). The negative electrode active material can also use elements such as Si and Sn that alloy with Li, materials containing the elements, etc. Among them, a composite material containing Si is preferred. As a preferred example of a composite material containing Si, Si-containing materials in which fine Si phases are dispersed in SiO2 phases, silicate phases such as lithium silicate, carbon phases, or silicide phases can be listed. As the negative electrode active material, graphite and Si-containing materials can be used in combination.

[0073] Similar to the case of the positive electrode 11, the binder contained in the negative electrode mixture layer 41 can also use fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., but preferably styrene-butadiene rubber (SBR) is used. In addition, the negative electrode mixture layer 41 preferably also contains CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, SBR is preferably used in combination with CMC or its salt, PAA or its salt. The negative electrode mixture layer 41 may also contain a conductive additive such as CNT.

[0074] [Separator]

[0075] The separator 13 can use a porous sheet with ion permeability and insulation. As specific examples of the porous sheet, microporous films, woven fabrics, non-woven fabrics, etc. can be listed. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are preferred. The separator 13 can be a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance such as aramid resin can be formed on the surface of the separator 13.

[0076] A filler layer containing an inorganic filler may be formed on the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphate compounds. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13.

[0077] Example

[0078] Hereinafter, the present disclosure will be further described through examples, but the present disclosure is not limited to these examples.

[0079] <Example 1>

[0080] [Synthesis of lithium transition metal composite oxides]

[0081] A composite hydroxide containing Ni, Co, and Mn is synthesized by a coprecipitation method and heat-treated at 400° C. to obtain a composite oxide. The oxide, lithium hydroxide, calcium hydroxide as a raw material of the metal element M1, and niobium pentoxide and titanium oxide as raw materials of the metal raw material M2 are mixed so that the molar ratio of the metal element (Me) in the composite oxide to Li in the lithium hydroxide (Li / Me ratio) is 1:1.040.

[0082] The mixture was put into a calcining furnace and calcined in three stages. In the calcining process, the temperature was raised from room temperature to 500°C at a heating rate of 2°C / min under an oxygen flow with an oxygen concentration of 95% (2 mL / min per 10 cM2 and a flow rate of 5 L / min per 1 kg of the mixture). Then, the temperature was raised from 500°C to 680°C at a heating rate of 1.5°C / min, and calcined from 680°C to 750°C at a heating rate of 1°C / min, and then kept at 750°C for 3 hours. The calcined product was crushed and washed with water, and then vacuum dried at 170°C to obtain a lithium transition metal composite oxide.

[0083] The obtained lithium transition metal composite oxide was analyzed by ICP-AES. As a result, the content of Ni was 89.9 mol%, the content of Co was 3.0 mol%, the content of Mn was 6.0 mol%, the content of Ca was 0.4 mol%, the content of Nb was 0.2 mol%, and the content of Ti was 0.5 mol% relative to the total amount of metal elements other than Li. In addition, the volume-based D50 of the composite oxide obtained by measuring with water as the dispersion medium using MT3000II manufactured by Microtrac Bell was 12 μm. By SEM images, it was confirmed that the composite oxide was a secondary particle formed by the aggregation of primary particles, and by TEM-EDX, it was confirmed that Ca, Nb and Ti were present on the surface of the primary particles.

[0084] [Preparation of AB dispersion]

[0085] Acetylene black (AB-1) with an average particle size (average length) of 19 nm and an average aspect ratio of 1.7 was used as a conductive aid, and polyvinyl pyrrolidone (PVP) was used as a dispersant. The conductive aid and the dispersant were dry-mixed at a mass ratio of 10:1 to obtain a powder, which was added to N-methyl-2-pyrrolidone (NMP) and dispersed using a ball mill to obtain a conductive aid dispersion (AB-1 dispersion) containing about 10% by mass of the conductive aid.

[0086] [Production of positive electrode]

[0087] The above-mentioned lithium transition metal composite oxide is used as a positive electrode active material. The positive electrode active material, AB dispersion (AB-1 dispersion) and polyvinylidene fluoride (PVDF) are mixed at a solid content mass ratio of 100:1:1 excluding the dispersant, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode mixture slurry. The positive electrode mixture slurry is applied to both sides of a positive electrode core body composed of aluminum foil, and after the coating film is dried, the coating film is rolled using a roller and cut into a specified electrode size to obtain a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode core body. It should be noted that an exposed portion where the surface of the positive electrode core body is exposed is provided on a part of the positive electrode.

[0088] [Production of negative electrode]

[0089] Natural graphite and silicon compounds are used as negative electrode active materials. Dispersions of natural graphite, silicon compounds, sodium carboxymethyl cellulose (CMC-Na), and styrene-butadiene rubber (SBR) are mixed at a solid content mass ratio of 95:5:1:1, and water is used as a dispersion medium to prepare a negative electrode mixture slurry. The negative electrode mixture slurry is applied to both sides of a negative electrode core body composed of copper foil, and after the coating film is dried, the coating film is rolled using a roller and cut into a specified electrode size to obtain a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode core body. It should be noted that an exposed portion where the surface of the negative electrode core body is exposed is provided on a part of the negative electrode.

[0090] [Preparation of non-aqueous electrolyte]

[0091] Ethylene carbonate (EC), ethyl methyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4 (25° C.), and LiPF6 was dissolved in the obtained mixed solvent at a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0092] [Fabrication of test battery (non-aqueous electrolyte secondary battery)]

[0093] An aluminum lead is installed on the exposed portion of the positive electrode, and a nickel lead is installed on the exposed portion of the negative electrode, and the positive electrode and the negative electrode are wound into a spiral shape through a polyolefin separator to prepare a wound electrode body. The electrode body is housed in a bottomed cylindrical outer can, the nonaqueous electrolyte is injected, and then the opening of the outer can is blocked with a sealing body to obtain a test battery.

[0094] <Example 2>

[0095] The average fiber diameter is 12nm, the average fiber length is 1μm, the average aspect ratio is 83 times, and the BET specific surface area is 220m 2 A test cell was prepared in the same manner as in Example 1 except that MWCNT (CNT-1) of 0.5 / g was used as the conductive additive for the positive electrode instead of AB-1 and the solid content of CNT-1 was 0.5 parts by mass relative to 100 parts by mass of the positive electrode active material. The MWCNT dispersion was prepared as follows.

[0096] [Preparation of MWCNT dispersion]

[0097] As described above, CNT-1 as a conductive aid, hydrogenated nitrile rubber (H-NBR) in which a copolymer of acrylonitrile and butadiene is hydrogen-substituted as a dispersant, and polyvinylpyrrolidone (PVP) also as a dispersant are mixed in a mass ratio of 6:1:1, added to N-methyl-2-pyrrolidone (NMP), and kneaded using a ball mill to obtain a conductive aid dispersion (CNT-1 dispersion) containing approximately 3% by mass of the conductive aid.

[0098] <Example 3>

[0099] A test cell was prepared in the same manner as in Example 2 except that a CNT-2 dispersion was used as the conductive auxiliary agent for the positive electrode instead of the CNT-1 dispersion. The CNT-2 dispersion was prepared as follows.

[0100] [Preparation of MWCNT dispersion]

[0101] CNT-1 as a conductive aid and polyvinyl pyrrolidone (PVP) as a dispersant were mixed in a mass ratio of 3:1, added to N-methyl-2-pyrrolidone (NMP), and kneaded using a ball mill to obtain a conductive aid dispersion (CNT-2 dispersion) containing approximately 3% by mass of the conductive aid.

[0102] <Example 4>

[0103] A composite hydroxide containing Ni, Co, Mn and Al is synthesized by a coprecipitation method, and a heat treatment is performed at 400°C to obtain a composite oxide. In addition, calcium hydroxide and strontium hydroxide are used as raw materials for the metal element M1, and zirconium oxide is used as the raw material for the metal element M2. Otherwise, a test cell is made in the same manner as in Example 1. It should be noted that the obtained lithium transition metal composite oxide is analyzed by ICP-AES, and the results show that, relative to the total amount of metal elements other than Li, the content of Ni is 90.3 mol%, the content of Co is 3.0 mol%, the content of Mn is 5.0 mol%, the content of Al is 1.0 mol%, the content of Ca is 0.2 mol%, the content of Sr is 0.1 mol%, and the content of Zr is 0.4 mol%.

[0104] <Example 5>

[0105] A test cell was prepared in the same manner as in Example 4 except that the CNT-3 dispersion was used as the conductive auxiliary agent. The MWCNT-3 dispersion was prepared as follows.

[0106] [Preparation of MWCNT dispersion]

[0107] The average fiber diameter of the conductive additive is 9 nm, the average fiber length is 1 μm, the average aspect ratio is 111 times, and the BET specific surface area is 260 m 2 / g of MWCNT (CNT-2) and polyvinyl pyrrolidone (PVP) as a dispersant were mixed in a mass ratio of 3:1, added to N-methyl-2-pyrrolidone (NMP), and kneaded using a ball mill to obtain a conductive aid dispersion (CNT-3 dispersion) with a conductive aid content of approximately 3% by mass.

[0108] <Example 6>

[0109] A test cell was prepared in the same manner as in Example 3 except that the material prepared in Example 4 was used as the positive electrode active material.

[0110] <Example 7>

[0111] A composite hydroxide containing Ni and Mn is synthesized by a coprecipitation method, and a heat treatment is performed at 400°C to obtain a composite oxide. In addition, calcium hydroxide is used as a raw material for the metal element M1, and niobium pentoxide and zirconium oxide are used as raw materials for the metal element M2. Otherwise, a test cell is made in the same manner as in Example 1. It should be noted that the obtained lithium transition metal composite oxide is analyzed by ICP-AES, and the results show that the content of Ni is 90.1 mol%, the content of Mn is 9.0 mol%, the content of Ca is 0.3 mol%, the content of Nb is 0.4 mol%, and the content of Zr is 0.2 mol%, relative to the total amount of metal elements other than Li.

[0112] <Comparative Example 1>

[0113] In the synthesis of the lithium transition metal composite oxide, the metal element M1 raw material and the metal element M2 raw material were not added, and the AB-0 dispersion was used instead of the AB-1 dispersion as the conductive auxiliary agent of the positive electrode, and a test cell was prepared in the same manner as in Example 1. It should be noted that the AB-0 dispersion was adjusted as follows.

[0114] [Preparation of AB dispersion]

[0115] Acetylene black (AB-0) with an average particle size (average length) of 23 nm and an average aspect ratio of 1.5 was used as a conductive aid, and polyvinyl pyrrolidone (PVP) was used as a dispersant. The conductive aid and the dispersant were dry-mixed at a mass ratio of 10:1 to obtain a powder, which was added to N-methyl-2-pyrrolidone (NMP) and dispersed using a ball mill to obtain a conductive aid dispersion (AB-0 dispersion) containing about 10% by mass of the conductive aid.

[0116] <Comparative Example 2>

[0117] A test cell was prepared in the same manner as in Example 1 except that the metal element M1 raw material and the metal element M2 raw material were not added during the synthesis of the lithium transition metal composite oxide.

[0118] <Comparative Example 3>

[0119] A test cell was prepared in the same manner as in Comparative Example 1 except that calcium hydroxide was added as a raw material of the metal element M1 during the synthesis of the lithium transition metal composite oxide so that the Ca content was 0.3 mol %.

[0120] <Comparative Example 4>

[0121] A composite hydroxide containing Ni, Co, Mn and Al was synthesized by a coprecipitation method and heat treated at 400°C to obtain a composite oxide. In addition, zirconium oxide was added as a raw material of the metal element M2 in the synthesis of the lithium transition metal composite oxide so that the Zr content was 0.4 mol%. Other than this, a test battery was prepared in the same manner as in Comparative Example 3.

[0122] <Comparative Example 5>

[0123] A test cell was prepared in the same manner as in Comparative Example 1, except that a composite hydroxide containing Ni and Mn was synthesized by a coprecipitation method and a composite oxide was obtained by heat treatment at 400°C. It should be noted that the obtained lithium transition metal composite oxide was analyzed by ICP-AES, and the result showed that the content of Ni was 91.0 mol% and the content of Mn was 9.0 mol% relative to the total amount of metal elements other than Li.

[0124] <Comparative Example 6>

[0125] In the synthesis of lithium transition metal composite oxide, calcium hydroxide was added as the metal element M1 raw material so that the Ca content was 0.3 mol%, and niobium pentoxide and zirconium oxide were added as the metal element M2 raw materials so that the Nb content was 0.4 mol% and the Zr content was 0.2 mol%. Except for this, the test battery was prepared in the same manner as Comparative Example 5.

[0126] The capacity, reaction resistance and DC resistance of each test battery of the above-mentioned examples and comparative examples were measured, and the evaluation results are shown in Table 1. The evaluation results (reaction resistance and DC resistance) shown in Table 1 are relative values ​​when the values ​​of the test battery of Comparative Example 1 are set to 100.

[0127] [Capacity measurement]

[0128] Repeat operation A and operation B twice and confirm the capacity. Operation A is to charge the above test battery at a constant current of 0.2It at a temperature environment of 25°C until the battery voltage reaches 4.2V, and to charge at a constant voltage of 4.2V until the current value reaches 1 / 50It. Operation B is to discharge at a constant current of 0.2It until the battery voltage reaches 2.5V.

[0129] [Evaluation of reaction resistance (Rct)]

[0130] The test battery with confirmed capacity was charged at a constant current of 0.2 It at a temperature of 25°C until the battery voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current value reached 1 / 50 It. Then, the AC impedance of the test battery was measured at a temperature of 25°C, a frequency of 0.01 Hz to 100,000 Hz, and an applied voltage of 10 mV, and the reaction resistance Rct at 25°C was obtained by fitting the equivalent circuit of the Nyquist plot.

[0131] [Evaluation of DC resistance (DCR)]

[0132] The test battery with confirmed capacity was charged at a constant current of 0.2 It at a temperature of 25°C until the battery voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current value reached 1 / 50 It, and then discharged at a constant current of 0.2 It until the capacity reached 50% of the capacity (SOC50%), and then a constant current of 0.5 It was applied to the test battery for 10 seconds. The DC resistance DCR was calculated by dividing the potential difference generated at this time by the current value.

[0133] [Table 1]

[0134]

[0135] As shown in Table 1, the reaction resistance and DC resistance of all test batteries of the embodiment are lower than those of the test batteries of the comparative example, and it can be understood that the resistance reduction effect of the positive electrode active material of the embodiment is excellent. It can be seen from Comparative Examples 1 to 3 and 5 that when the metal elements M1 and M2 are not added to the lithium transition metal composite oxide, a sufficient resistance reduction effect cannot be obtained. Even if the metal elements M1 and M2 are added to the lithium transition metal composite oxide, when the average particle size of the conductive additive is greater than 20nm, although the reaction resistance can be reduced to the same level as the embodiment, the DC resistance is increased compared to Comparative Example 1 (Comparative Examples 4 and 6).

[0136] That is, only when the metal elements M1 and M2 are introduced into the interface between the primary particles constituting the positive electrode active material and a conductive additive having an average particle size / average fiber diameter of 20 nm or less is used, the reaction resistance and the DC resistance can be significantly reduced at the same time. In addition, when CNT having an average fiber diameter of 20 nm or less is used as a conductive additive, an excellent resistance reduction effect can be obtained with a smaller addition amount than AB.

[0137] The present disclosure is further described through the following embodiments.

[0138] Scheme 1: A positive electrode for a non-aqueous electrolyte secondary battery, comprising a positive electrode core and a positive electrode mixture layer formed on the positive electrode core, the positive electrode mixture layer comprising a positive electrode active material, a conductive aid and a binder, the positive electrode active material comprising a lithium transition metal composite oxide, the lithium transition metal composite oxide having a layered structure and containing 75 mol % or more of Ni relative to the total molar amount of metal elements other than Li, the lithium transition metal composite oxide being secondary particles formed by aggregation of primary particles, at the interface between the primary particles inside the secondary particles, there is at least one selected from the group consisting of Ca and Sr and at least one selected from the group consisting of W, Mo, Ti, Si, Nb and Zr, the conductive aid containing carbon and comprising at least one selected from the group consisting of granular carbon materials having an average particle size of less than 20 nm and fibrous carbon materials having an average fiber diameter of less than 20 nm.

[0139] Scheme 2: The positive electrode for a non-aqueous electrolyte secondary battery according to Scheme 1, wherein the lithium transition metal composite oxide is of the general formula Li x Ni a Co b Mn c Al d M1 e M2 f O 2-y The composite oxide shown in the formula, wherein 0.95<x<1.05, 0.75≤a≤0.95, 0≤b≤0.15, 0≤c≤0.25, 0≤d≤0.03, 0<e≤0.01, 0<f≤0.03, 0≤y<0.05, a+b+c+d+e+f=1, M1 is at least one element selected from the group consisting of Ca and Sr, and M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr.

[0140] Scheme 3: The positive electrode for a non-aqueous electrolyte secondary battery according to Scheme 1 or 2, wherein a particle of the general formula M1 is fixed to the interface between the primary particles inside the secondary particles. α M2 β O γ The compound shown in the formula, wherein 1≤α≤2, 1≤β≤5, 4≤γ≤9, M1 is at least one element selected from the group consisting of Ca and Sr, and M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr.

[0141] Aspect 4: The positive electrode for a non-aqueous electrolyte secondary battery according to any one of aspects 1 to 3, wherein the particulate carbon material is acetylene black having an average particle size of 20 nm or less.

[0142] Aspect 5: The positive electrode for a non-aqueous electrolyte secondary battery according to any one of aspects 1 to 4, wherein the fibrous carbon material is a carbon nanotube having an average fiber diameter of 10 nm or less.

[0143] Aspect 6: The positive electrode for a non-aqueous electrolyte secondary battery according to any one of aspects 1 to 5, wherein the average aspect ratio of the fibrous carbon material is 50 or more.

[0144] Aspect 7: The positive electrode for a non-aqueous electrolyte secondary battery according to any one of aspects 1 to 6, wherein the content of the conductive auxiliary agent is 1 part by mass or less relative to 100 parts by mass of the lithium-transition metal composite oxide.

[0145] Aspect 8: The positive electrode for a non-aqueous electrolyte secondary battery according to any one of aspects 1 to 7, comprising a nitrile group-containing rubber as a dispersant for the conductive auxiliary agent.

[0146] Aspect 9: A nonaqueous electrolyte secondary battery comprising the positive electrode according to any one of aspects 1 to 8, a negative electrode, and a nonaqueous electrolyte.

[0147] Description of Reference Numerals

[0148] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove part, 23 internal terminal plate, 24 lower valve body, 25 insulating part, 26 upper valve body, 27 cover, 28 sealing gasket, 30 positive electrode core, 31 positive electrode mixture layer, 40 negative electrode core, 41 negative electrode mixture layer.

Claims

1. A positive electrode for a non-aqueous electrolyte secondary battery, comprising a positive electrode core and a positive electrode mixture layer formed on the positive electrode core, The positive electrode mixture layer comprises a positive electrode active material, a conductive additive and a binder. The positive electrode active material includes a lithium transition metal composite oxide having a layered structure and containing 75 mol % or more of Ni relative to the total molar amount of metal elements other than Li. The lithium transition metal composite oxide is a secondary particle formed by aggregation of primary particles. At the interface between the primary particles inside the secondary particles, at least one selected from the group consisting of Ca and Sr and at least one selected from the group consisting of W, Mo, Ti, Si, Nb and Zr are present, The conductive aid contains carbon and includes at least one selected from the group consisting of a granular carbon material having an average particle diameter of 20 nm or less and a fibrous carbon material having an average fiber diameter of 20 nm or less.

2. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The lithium transition metal composite oxide is of the general formula Li x Ni a Co b Mn c Al d M1 e M2 f O 2-y The composite oxide shown in the formula, wherein 0.95<x<1.05, 0.75≤a≤0.95, 0≤b≤0.15, 0≤c≤0.25, 0≤d≤0.03, 0<e≤0.01, 0<f≤0.03, 0≤y<0.05, a+b+c+d+e+f=1, M1 is at least one element selected from the group consisting of Ca and Sr, and M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr.

3. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein At the interface between the primary particles inside the secondary particles, a particle of the general formula M1 is fixed. α M2 β O γ The compound shown in the formula, wherein 1≤α≤2, 1≤β≤5, 4≤γ≤9, M1 is at least one element selected from the group consisting of Ca and Sr, and M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr.

4. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The granular carbon material is acetylene black having an average particle size of 20 nm or less.

5. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The fibrous carbon material is a carbon nanotube having an average fiber diameter of 10 nm or less.

6. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The average aspect ratio of the fibrous carbon material is 50 or more.

7. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The content of the conductive auxiliary agent is 1 part by mass or less relative to 100 parts by mass of the positive electrode active material. 8 . The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1 , comprising a nitrile group-containing rubber as a dispersant for the conductive auxiliary agent. 9 . A nonaqueous electrolyte secondary battery comprising the positive electrode according to claim 1 , a negative electrode, and a nonaqueous electrolyte.

Citation Information

Patent Citations

  • Positive electrode active material for nonaqueous electrolyte secondary battery and method for manufacturing the same, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2018129221A